Beginning teachers' observations of peers - the values, limitations, and suggestions from the perspectives of the insiders = Giá trị, hạn chế, và gợi ý cho việc dự giờ lẫn nhau của giáo viên mới vào nghề. M.A Thesis Linguistics: 60 14 10 - Đỗ, Thị Phương Thúy (University of Foreign Languages and International studies, 2017)
79 p. + CD-ROM